Purpurin as a promising anticancer agent: A review of preclinical evidence - Fui Ling, Voon; Yu Zhao, Lee; Xiao Ying, Ooi; Charlotte Zi Ern, Tay; Ji Wei, Tan; Chau Ling, Tham; Yu-Cheng, Ho; Ming Tatt, Lee (Elsevier B.V., 2026)
Purpurin, a naturally occurring anthraquinone pigment, has gained attention for its promising anticancer properties. This systematic-narrative hybrid review summarises current preclinical evidence on its mechanisms of action, pharmacology, and translational potential. Literature searches were conducted using PubMed, Web of Science, Scopus, and Google Scholar up to June 2025. Purpurin demonstrates selective cytotoxicity across multiple cancer models through redox imbalance, mitochondrial dysfunction, inhibition of PI3K/AKT signalling, and upregulation of the tumour suppressor LHPP. It also interferes with amino acid and glutamine metabolism and suppresses oncogenic protein aggregation. As a photosensitiser, purpurin enhances photodynamic therapy through light-activated ROS generation. Despite these promising mechanistic insights, its clinical applicability remains limited by poor aqueous solubility, rapid metabolism, and insufficient pharmacokinetic and toxicological data. Early in vivo studies indicate favourable safety, and emerging nanoparticle-based delivery systems show potential to improve bioavailability and tumour targeting. Collectively, current findings highlight purpurin as a compelling candidate for further development in oncology, particularly as part of combination or photo-enhanced therapeutic approaches. Continued research is required to address existing pharmacological gaps and to evaluate purpurin in clinically relevant models.